High p16INK4a immunoexpression is not HPV dependent in oral leukoplakia - Tomo, Saygo [UNESP]; Biss, Stephanye Pinto [UNESP]; Crivelini, Marcelo Macedo [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Biasoli, Éder Ricardo [UNESP]; Tjioe, Kellen Cristine [UNESP]; Bernabé, Daniel Galera [UNESP]; Villa, Luisa Lina; Miyahara, Glauco Issamu [UNESP] (Elsevier, 2020)
Objective: To evaluate the prevalence of HPV DNA detection in fresh tissue from oral leukoplakia by Linear Array assay, and its correlation with p16INK4a immunoexpression in the northwest region of the São Paulo state, Brazil. Patients and methods: Fifty patients diagnosed with oral leukoplakia were included in the study. Sociodemographic, clinicopathologic and lifestyle data, fresh tissue and formalin fixed paraffin embedded (FFPE) tissue samples were collected. The fresh tissue was stored at -80 °C and then submitted to further viral DNA detection by the Linear Array method. Immunohistochemical analysis for the p16INK4a expression was performed. Results: Of the 50 patients included in the study, 62 % were men, and the age ranged from 25 to 82 years. Twenty-three (46 %) were elderly, 46 % were middle-aged adults, and only 12 % were young adults. Most patients were smokers (76 %), 14 % were former smokers, and 10 % were non-smokers. Most patients (56 %) were current drinkers, 22 % were ex-drinkers and 22 % were non-drinkers. Thirty-two percent of the lesions presented some degree of dysplasia. No lesions were positive to HPV by Linear Array detection. Thirty (60 %) OL had p16-low immunoexpression and 20 (40 %) had p16-high immunoexpression. Conclusion: HPV was not identified in the population studied. The high p16INK4a immunoexpression is not dependent on HPV in oral leukoplakia. Broader epidemiological studies are required to clarify the geographic variability in the prevalence of HPV in head and neck squamous cell carcinoma and oral potentially malignant lesions.
Keywords: Human papillomavirus; Oral leukoplakia; p16(INK4A); Polymerase chain reaction